CORN HUSK FERMENTATION WITH BREWERY WASTE YEAST AS FISH MEAL SUBSTITUTE IN THE DIET OF AFRICAN CATFISH (Clarias gariepinus) FINGERLINGS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study was conducted to evaluate the effect of partial substitution of fish-meal (FM) with two types of fermented animal by-products (fish and poultry offal‟s wastes) on growth performance, microbiological, and fish quality of African catfish (Clarias gariepinus). Fish offal‟s silage (FOS) and poultry offal‟s silage (POS) were fermented by Lactobacillus acidophilus. Five isonitrogenous (34.3% crude protein) diets were formulated to comprise two levels of fermented fish offal (20% and 40%), two levels of fermented poultry offal (20% and 40%) wastes, and 100% fish meal as a control. Ninety hatcheries bred African catfish were randomly distributed into 5 equal groups every 18 fish in three replicate (6 fish/ replicate aquaria). Each of the diets was fed to triplicate groups of African catfish with mean initial weight (MIW) 52g ± 0.01 at 5% body weight in glass aquaria (30 x 30 x70 cm) twice daily (morning and evening) for 12 weeks. The results showed that fish in the fourth group fed on diet supplemented with 20 % POS recorded the best feed conversion ratio (FCR) (1.77±0.1), protein efficiency ratio (PER) (3.51±0.06), incidence of cost (IC) (16.3±0.37), and profit index (PI) (3.51±0.06). Fish in group four as well had the least total bacterial count, coliform, and mold & yeast. The least lactic acid bacteria count and the best overall acceptance were detected also in the fourth group as compared to other groups except diet 1(control) which means it can be used safely without significantly affecting public health or consumer acceptance.